Pengaruh Keterampilan, Komunikasi dan Pengalaman Kerja terhadap Peluang Kerja di Era Pandemi Covid-19 Bagi Warga Urbanisasi di Perumahan Taman Cikarang Indah 2 Blok D - Sumajianto Sumajianto; Sri Wahyuningsih (Journal on Education, 2023)
The problem in this study is how the influence of skills, communication and work experience partially and simultaneously on job opportunities. And which variables are the most dominant that affect job opportunities for urbanized residents in Taman Cikarang Indah 2 Block D Housing. This study was conducted by distributing questionnaires shown to urbanized residents in Taman Cikarang Indah 2 Block D Housing which amounted to 100 respondents, sampling in this study using purposive sampling techniques. The data processing method uses multiple linear regression methods. The data analysis used is descriptive quantitative, namely because this research data is in the form of numbers and analysis using statistics so that a conclusion can be obtained from the results of the study.